Q-switched double frequency Nd:YAG 532-nm nanosecond laser vs. double frequency Nd:YAG 532-nm picosecond laser for the treatment of solar lentigines in Asians - Vasanop Vachiramon (2019)
© 2018, Springer-Verlag London Ltd., part of Springer Nature. Solar lentigines are common pigmentary lesions. Q-switched lasers are effective treatment options but postinflammatory hyperpigmentation (PIH) is common in darker skin. The objective of the study is to compare the efficacy and safety in solar lentigines of Asian skin treated by Q-switched potassium titanyl phosphate (KTP) 532-nm nanosecond laser vs. KTP 532-nm picosecond laser for the treatment of solar lentigines in Asians. Thirty patients with at least 2 solar lentigines on the upper extremities were enrolled. A total of 30 paired lentiginous lesions were randomly treated with a single treatment of either Q-switched KTP 532-nm nanosecond laser vs. KTP 532-nm picosecond laser. In terms of efficacy, mean luminance score was evaluated at baseline, at 6th, and 12th week. Degree of pigment clearance was assessed by a blinded physician and the patients. Satisfaction score was rated by patients using visual analogue scale. Adverse events were also recorded. Twenty-eight patients completed the study. Both lasers showed significant improvement in mean luminance score from baseline (p < 0.05). Likewise, there was no significant difference in pigment clearance between two lasers either assessed by physician or patients. However, patients’ satisfaction score was significantly higher with the picosecond laser (p = 0.014). Adverse events and pain were not different between groups. Q-switched KTP 532-nm nanosecond laser and KTP 532-nm picosecond laser are safe and effective for treating solar lentigines in Asians. Based on cost-effectiveness, Q-switched KTP 532-nm nanosecond laser remains the main treatment while KTP 532-nm picosecond laser can be considered as a treatment option.